2015
DOI: 10.1016/j.rmed.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of chronic obstructive pulmonary disease in HIV infected patients in an African country with low level of tobacco smoking

Abstract: HIV infection is possibly a risk factor for COPD in this setting. The careful investigation of the determinants of COPD during routine diagnosis and care of people with HIV infection can aid the detection, further investigation, and improvement of the management of this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 23 publications
4
40
1
Order By: Relevance
“…Cameroon investigators measured lower COPD prevalence among PLWH (2.2%) but describe similar associations between HIV, tuberculosis and COPD[21]. Their lower prevalence may be explained by a comparatively younger population with a lower smoking prevalence.…”
Section: Discussionmentioning
confidence: 94%
“…Cameroon investigators measured lower COPD prevalence among PLWH (2.2%) but describe similar associations between HIV, tuberculosis and COPD[21]. Their lower prevalence may be explained by a comparatively younger population with a lower smoking prevalence.…”
Section: Discussionmentioning
confidence: 94%
“…The resultant immune dysregulation is associated with end-organ damage [58,6264], and may be important mechanistically in CLD development. HIV itself is an independent risk factor for COPD among adults [6,65,66]. Preliminary data suggest that HIV is also independently associated with CLD in children and adolescents [12*,15*,18**].…”
Section: Risk Factors For Hiv-associated Chronic Lung Disease Among Amentioning
confidence: 99%
“…Findings from two observational studies suggested ART use was associated with an increased risk of COPD, 5,6 results from another study showed a lower incidence of COPD among ART users, 7 and results from other studies showed no association. 811 All these studies were limited by their observational designs, in which ART use might be confounded by factors such as socioeconomic status, adherence to medical therapy, and other health behaviours that might affect both the likelihood of ART use and COPD risk.…”
Section: Introductionmentioning
confidence: 99%